Kehadiran Pemilih Di TPS (Tempat Pemungutan Suara) dalam Pilkada Serentak Bulan Desember Tahun 2020 - Santosa, Santosa (Ridwan Institute, 2021)
This study aims to analyze how the level of Voter Attendance at polling stations (TPS) in the December 2020 Regional Elections coincided with the COVID-19 Pandemic. The method used in this research is survey research with cross sectional research design through questionnaires distributed using google form distributed through Watshap Group that can reach out of Java for four days with creteria that at that time the region held simultaneous elections. The sample used in this study was probabilitysampling. The population in this study was all 130 respondents who filled google from being used as respondents. Conclusion On Characteristic Variables, novice respondents are still low at 5 (3.8%) first-time respondents participated in the Simultaneous Elections, in line with the age indicatorthat the age of novicevoters is usi a 17 Years - 20 Years obtained 1 (0.8%) Respondents. In the concurrent Election Variables that the attendance rate is 120 (92.3%) respondents stated that they were present at the polling station to exercise their voting rights in the 2020 Regional Elections. In the Covid 19 Pandemic Variable,respondents currentlynumber 85(65.4%) respondents stated in the Red Zone and Health Protocol in tps number 95 (73.1%) respondents stated Already and Very Maximal in applying Prokes in tps where respondents choose.